A prospective study on pain score with transperineal prostatic gold seed fiducial implantation under local anesthetic alone - Tang, Colin I.; Sethukavalan, Perakaa; Cheung, Patrick; Morton, Gerard; Pang, Geordi; Loblaw, D. Andrew (Canadian Urological Association Journal, 2013)
Background: The purpose of this study was to monitor patient pain score with transperineal prostatic gold seed implantation in the absence of conscious sedation. Methods: All patients who were scheduled for image-guided external beam radiation (IGRT) and referred for gold seed fiducials were eligible to participate. Gold seed implants were performed by two radiation oncologists between December 2007 and April 2008. Patients received only local and deep anesthetic. No patients had prophylactic IV cannulation for the procedure. Three gold seeds were inserted transperineally into the prostate. A visual analogue scale from 0 to 10 was used to assess the pain at baseline, local and deep anesthetic infiltration, with each seed drop, and after the completion of the procedure. Results: A total of 30 patients were accrued to this study. The highest recorded increase in pain score was at the time point of deep local anesthesia, at which the mean pain score was 3.8. The mean pain scores at each seed drop were 0.8 (standard deviation [SD]=1.24), 1 (SD=1.26), and 0.5 (SD=0.90), respectively. All gold seed insertion procedures were well-tolerated, with no patient shaving significant pain post-procedure, and no significant procedural complications. There were only slight increases in dysuria, urinary frequency, constipation, urinary retention and flatulence in 7 patients – none of which required intervention. Interpretation: Transperineal ultrasound-guided gold seed implantation without conscious sedation is well-tolerated and associated with a low complication rate. It is a convenient outpatient procedure obviating the need for resource intensive postoperative monitoring.